The effects of war-related experiences on mental health symptoms of individuals living in conflict zones: a longitudinal study - Doron Amsalem; Shilat Haim-Nachum; Amit Lazarov; Yossi Levi-Belz; John C. Markowitz; Maja Bergman; Alexandra Klein Rafaeli; Lisa A. Brenner; Nitsa Nacasch; Milton L. Wainberg; Ido Lurie; Shlomo Mendlovic; et al. (Scientific Reports)
Abstract On October 7, 2023, a large-scale attack in southern Israel and the subsequent war resulted in extensive loss of life and injuries, with many individuals experiencing traumatic losses, such as family members or close friends being killed or kidnapped. This study aims to longitudinally examine its effects on mental health, specifically, clinical symptoms of anxiety, depression, and posttraumatic stress disorder (PTSD). We anticipated greater symptom severity among individuals who experienced traumatic loss, were forcibly displaced, or suffered income loss, as well as among women and members of ethnic minorities. This three-wave online survey study assessed mental health symptoms in a sample of 1052 individuals, aged 18–40, residing in conflict zones in Israel from February 2024 (day 1), through March 2024 (day 30), to May 2024 (day 90). Symptoms of anxiety, depression, and PTSD were measured using the Generalized Anxiety Disorder-7 (GAD-7), Patient Health Questionnaire-9 (PHQ-9), and Primary Care PTSD Screen (PC-PTSD). Individuals experiencing traumatic losses, forced displacement, or economic hardships, as well as females, consistently demonstrated higher rates of anxiety, depression, and PTSD symptoms compared to those without such experiences or to males, across all time points (F values ranged from 17.7 to 215.3, p < .001). For ethnic minorities (Arab and other), as compared to Jewish, anxiety and depression symptoms were higher at every time point (F = 8.3–97.1, p = .004 to < .001). This study highlights the urgent need for targeted mental health interventions in conflict zones, particularly for affected individuals. Further research should expand these findings to broader populations.